Emerging agents and regimens for polycythemia vera and essential thrombocythemia - Rory M. Shallis; Nikolai A. Podoltsev (BMC, 2021)
Abstract Polycythemia vera (PV) and essential thrombocythemia (ET) are both driven by JAK-STAT pathway activation and consequently much of the recent research efforts to improve the management and outcomes of patients with these neoplasms have centered around inhibition of this pathway. In addition to newer JAK inhibitors and improved interferons, promising novel agents exploiting a growing understanding of PV and ET pathogenesis and disease evolution mechanisms are being developed. These agents may modify the disease course in addition to cytoreduction. Histone deacetylase, MDM2 and telomerase inhibitors in patients with PV/ET have demonstrated clinically efficacy and serve as chief examples. Hepcidin mimetics, limiting iron availability to red blood cell precursors, offer an exciting alternative to therapeutic phlebotomy and have the potential to revolutionize management for patients with PV. Many of these newer agents are found to improve hematologic parameters and symptom burden, but their role in thrombotic risk reduction and disease progression control is currently unknown. The results of larger, randomized studies to confirm the early efficacy signals observed in phase 1/2 trials are eagerly awaited.